CORPORATE CRIMINAL LIABILITY FOR CRIMINAL NEGLIGENCE OF FOREST AND LAND FIRE CAUSES: Decision Study: Number 71/Pid B/LH/2021/PN Snt - Ganitri, Ni Nyoman Ayu Ratih; Sugiartha, I Nyoman Gede; Setiabudhi, I Ketut Rai (jfpublisher, 2024)
During the globalization era, forest exploitation has become more frequent, one of them is burning land as a cause of rapid reduction in forest area. Forest and land fires caused by human activities can be categorized as legal acts, i.e. those occurrences or events that can trigger legal consequences. Therefore, forest and land burning is not included in ordinary criminal offenses. This research aims to analyze the arrangements for criminal liability for criminal negligence that causes forest and land fires (Ius Constitutum) and to analyze the considerations of the judges for negligence for causing forest and land fires in Decision Number 71/Pid B/LH/2021/PN Snt. The method used is a normative method with a statutory approach, legal concepts and theories. The result of this research is that criminal liability for the causes of forest and land fires can be identified from several legislations that have been established and are applicable at this time, both those committed intentionally and due to negligence, and both those committed by individuals and those committed by corporations. The Judges’ consideration in Decision Number: 71/Pid B/LH/2021/PN Snt, imposed a fine and additional punishment on the defendant that is PT Mega Anugrah Sawit. The judge only recognized the defendant’s guilt due to negligence, while from the facts of the trial there was an element of intent.